Sikap Kepala Sekolah dan Guru Terhadap Perpustakaan di SDN 01 Belakang Tangsi - Putri, Allya Mardilla; Ardoni, Ardoni (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
This study aims to describe the attitudes of the school principal and teachers toward the library at SDN 01 Belakang Tangsi. This research is a qualitative study with a descriptive approach. The informants were selected using purposive sampling, consisting of seven individuals: one school principal and six teachers. The research instrument used was an interview guideline. Data collection was conducted through interviews, and data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions. The results of study show that: First, both the school principal and teachers view the library and librarian as two important elements. Second, the reason the school has not hired a librarian until now is that the BOS (School Operational Assistance) fund cannot cover the libraian’s salary, and approval must be obtained from the BOS of the Education Office. Teachers have informed the principal that many students inquire about the library, and the teachers can only explain to the students that the library is inactive due to the lack of librarian to manage it. Teachers search for teaching references through textbooks, journals on the internet, and sometimes YouTube, while students only search for references through textbooks. Third, both the principal and teachers have taken steps to reactivate the library at SDN 01 Belakang Tangsi by holding a meeting to discuss the library’s reactivation. The principal has proposed to the Education Office regarding the need for a librarian to manage the library. In the meantime, teachers will manage the library by organizing a teacher duty roster until the confirmation from the Education Office regarding the librarian’s position is received.